Note—A Note on “Lot Size Scheduling on a Single Machine for Stochastic Demand” by Goyal - Vergin, Roger C. (Management Science, 1976)
A Note on “Lot Size Scheduling on a Single Machine for Stochastic Demand” by Goyal (Goyal, S. K. 1973. Lot size scheduling on a single machine for stochastic demand. Management Sci. 19 1322–1325).